If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 = 3z + -2 Reorder the terms: 7 = -2 + 3z Solving 7 = -2 + 3z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-3z' to each side of the equation. 7 + -3z = -2 + 3z + -3z Combine like terms: 3z + -3z = 0 7 + -3z = -2 + 0 7 + -3z = -2 Add '-7' to each side of the equation. 7 + -7 + -3z = -2 + -7 Combine like terms: 7 + -7 = 0 0 + -3z = -2 + -7 -3z = -2 + -7 Combine like terms: -2 + -7 = -9 -3z = -9 Divide each side by '-3'. z = 3 Simplifying z = 3
| -2(7-8n)=-110 | | 7(2x+6)=126 | | 10(1+2k)=490 | | x+1-2=2 | | 7x-3/3x=4 | | X+112+92=180 | | y-3x-12=0 | | 8+8x-7x=x+8 | | x^2+19x+50=0 | | 4x+1=5x-9 | | x^2+19x+50= | | (6y^2-43y-20)/(y-8) | | (6n^2)+7n-3=0 | | 8^3/2^9 | | 10=2x+16 | | 8x^3/2x^9 | | 5/9p=15 | | 4+x+(-17)=9 | | -39r-2=30 | | (3x-4)(x+2)=112 | | (12x+38)=(8x+1) | | 2x^2+3x+1=2x^2+9x+9-14 | | sinx+sqrt(2)=-sinx | | y=x^3-6 | | A=4nr^2 | | 4(x+3)=5x+28 | | 8(2x-1)=-32 | | 150(t)=16t^2+130t+s | | x+4=-24.3 | | 3u=8+u | | 2(4-12y)+y=-123 | | (x-2)(x+3)+(x-3)(x+2)=4(x+1) |